How digital storytelling builds visit intention in Jakarta's heritage tourism destinations: The mediating role of destination brand attitude.: Digital storytelling and visit intention in Jakarta's heritage tourism - Setyaningsih, Ratih Nur; Pratikto, Zulham Dwi (International Journal of Business, Law, and Education, 2026)
Digital storytelling has become a key strategy for strengthening the competitiveness of heritage tourism destinations in the digital era. Nevertheless, the mechanisms through which digital storytelling influences tourists' visit intention remain insufficiently explored. This research investigates the interrelationships among digital storytelling, destination brand awareness, perceived authenticity, destination brand attitude, and visit intention within Jakarta's heritage tourism destinations. Data were collected from 164 visitors through a structured questionnaire and analyzed using PLS-SEM. The findings indicate that digital storytelling, destination brand awareness, and perceived authenticity significantly enhance destination brand attitude but have no direct effect on visit intention. Instead, destination brand attitude fully mediates these relationships and is the strongest predictor of visit intention (β = 0.700). The model explains 74.9% of destination brand attitude and 62.1% of visit intention, highlighting the importance of destination branding in encouraging tourists' behavioral intentions.